Connective tissue panniculitis and vitiligo in a patient with stage IV melanoma achieving complete response to dabrafenib and trametinib combination therapy. Issue 6 (December 2021) - Gargiulo, Luigi; Chiara Tronconi, Maria; Grimaudo, Maria S.; Pavia, Giulia; Valenti, Mario; Manara, Sofia; Costanzo, Antonio; Borroni, Riccardo G.
Abstract : The combination of BRAF and MEK inhibitors, such as dabrafenib and trametinib, respectively, is an established treatment option for patients with advanced BRAF V600 -mutated melanoma. With the wide adoption of these therapies, a range of cutaneous adverse effects has been reported. We describe the case of a 47-year-old woman with BRAF V600E -mutated stage IV melanoma treated with dabrafenib and trametinib for 30 months who presented to our attention for painful skin lesions that had been present on her limbs since the start of targeted therapy. We also observed vitiligo-like lesions on the extensor surface of both legs. Despite achieving a complete oncological response, the patient had to discontinue the treatment because of persisting fever, nausea and painful skin nodules that significantly impaired her quality of life. The recognition of cutaneous signs of efficacy of such drugs for advanced melanoma is of primary importance in order to identify patients with potential long-term clinical benefits.